IMPLEMENTASI PROGRAM AKU BISA DALAM MEMBENTUK KEMANDIRIAN ANAK USIA DINI - Habibah Habibah (Educare : Jurnal Ilmu Pendidikan, 2022)
This research aims to examine efforts to train early childhood independence through the "Aku Bisa" program based on self-habituation. This research took the research site in Sinar Harapan Kindergarten, Jrebeng Wetan village, Kedopok subdistrict, Probolinggo city as the originator of the "Aku Bisa" program. To review the program, this study used a descriptive qualitative approach with the type of case study. Data analysis techniques used after data are collected through interviews and observations are data reduction, data display, and data verification. The results showed that the "Aku Bisa" program consists of routine activities carried out since students arrive at school until the learning time is over and evaluation with the student guardian every two months. The implication is that efforts to train children's independence will be successful if parents also support program activities and monitor their development